Alkyne–alkenyl coupling at a diruthenium complex. Issue 41 (30th September 2022) - Bresciani, Giulio; Boni, Serena; Zacchini, Stefano; Pampaloni, Guido; Bortoluzzi, Marco; Marchetti, Fabio
Abstract : Two types of uncommon hydrocarbyl ligands are built on a diruthenium scaffold via the room temperature coupling of a bridging alkenyl with a series of alkynes. Abstract : Dimetallic complexes are suitable platforms for the assembly of small molecular units, and the reactivity of bridging alkenyl ligands has been widely investigated to model C–C bond forming processes. Here, we report the unusual coupling of an alkenyl ligand, bridging coordinated on a diruthenium scaffold, with a series of alkynes, revealing two possible outcomes. The diruthenium complex [Ru2 Cp2 (Cl)(CO)(μ-CO)μ–η 1 :η 2 -C(Ph){CH(Ph)], 2, was prepared in two steps from [Ru2 Cp2 (CO)2 (μ-CO)μ–η 1 :η 2 -C(Ph){CH(Ph)]BF4, [1]BF4, in 69% yield. Then, the reaction of 2 with C2 (CO2 Me)2, promoted by AgCF3 SO3 in dichloromethane, afforded in 51% yield the complex [Ru2 Cp2 (CO)2 μ–η 3 :η 2 -C(Ph)CH(Ph)C(CO2 Me)C(CO2 Me)]CF3 SO3, [3 ]CF3 SO3, containing a ruthenacyclopentene-based hydrocarbyl ligand. On the other hand, 2 reacted with other alkynes and AgX salts to give the butadienyl complexes [Ru2 Cp2 (CO)2 μ–η 3 :η 2 -C(R)CH(R′)C(Ph)C(Ph)]X (R = R′ = H, [4 ]BF4 ; R = R′ = Me, [5 ]CF3 SO3 ; R = R′ = Ph, [6 ]CF3 SO3 ; R = Ph, R′ = H, [7 ]CF3 SO3 ), in 42–56% yields. All products were characterized by IR and NMR spectroscopy, and by single crystal X-ray diffraction in the cases of 2, [3 ]CF3 SO3 and [6 ]BF4 . DFT calculations highlighted the higher stability of [4–7 ] + -like structures with respect to the corresponding [3 ] + -like isomers. It is presumable that [3 ] + -like isomers initially form as kinetic intermediates, then undergo H-migration which is disfavoured in the presence of carboxylato substituents on the alkyne. Such hypothesis was supported by the computational optimization of the transition states for H-migration in the cases of R = R′ = H and R = R′ = CO2 Me.